EU's global gateway strategy and building a global consensus vis-a-vis BRI - Jagannath P. Panda (OrdnungsPolitisches Portal (OPO), 2022)
The Belt and Road Initiative paved the way for China to establish far-reaching trade relations and greater political influence across continents. Dominating the Indo-Pacific region by building up the dependence of the countries there on China is only part of the strategy. China's actions in this regard are observed with unease by researchers and practitioners. Various multilateral projects are trying to present an alternative in the Indo-Pacific region, including the EU's Global Gateway Strategy Project. What this strategy entails and how it can play a role in shaping global consensus on the BRI will be outlined below.
Keywords: 330; Belt and Road Initiative; China; Geopolitics; EU; Global Gateway Strategy; Indo-Pacific